Fungi Occurrence in Ready-to-Eat Hazelnuts (Corylus avellana) From Different Boreal Hemisphere Areas - Lombardi, Silvia Jane; Pannella, Gianfranco; Tremonte, Patrizio; Mercurio, Ida; Vergalito, Franca; Caturano, Costantino; Maiuro, Lucia; Iorizzo, Massimo; Succi, Mariantonietta; Sorrentino, Elena; Coppola, Raffaele (Frontiers in Microbiology, 2022)
The present study evaluated the fungal contamination of ready to eat dried hazelnuts considering for the first time the application of the same condition drying process of several hazelnut cultivars from different boreal hemisphere areas. 50 lots of hazelnuts (Corylus avellana) belonging to 8 cultivars from 7 regions of 4 countries were analysed to evaluate fungal microbiota describing not only the load levels but also the species diversity. For this purpose, a polyphasic approach consisting of morphological examination (optical and scanning electron microscope observation) and molecular characterization (PCR-DGGE analysis and sequence analyses of the internal transcribed spacer -ITS-) was performed. Results showing that different fungal populations occur in dried hazelnuts regardless of their geographical area of production. Although some varieties appear to be relatively less susceptible, species related to Aspergillus, such as A. commune and A. ochraceus, Penicillium, including P. commune, P. solitum and P. expansum, and Rhizopus, with R. stolonifer and R. oryzae have generally been found. A related character 'hazelnut cultivar - fungi' was found for species related to the genus Trichoderma and Fusarium, including F. oxyxporum, F. solani and F. falciforme. All 14 species found are known to host pathogenic strains. Therefore, their presence in a ready-to-eat product, such as dried hazelnuts, can pose a real danger to the consumer. Based on these considerations, the development of new protective strategies seems highly desirable. The species-level description of the contaminating fungal community acquired through this study is the starting point for the development of tailor-made protective biotechnologies.